A review of probiotics in the treatment of autism spectrum disorders: Perspectives from the gut–brain axis - Feng, Pengya; Zhao, Shuai; Zhang, Yangyang; Li, Enyao (Frontiers in Microbiology, 2023)
Autism spectrum disorders (ASD) are a class of neurodevelopmental conditions with a large societal impact. Despite existing evidence suggesting a link between ASD pathogenesis and gut–brain axis dysregulation, there is no systematic review of the treatment of probiotics on ASD and its associated gastrointestinal abnormalities based on the gut–brain axis. Therefore, we performed an analysis for ASD based on preclinical and clinical research to give a comprehensive synthesis of published evidence of a potential mechanism for ASD. On the one hand, this review aims to elucidate the link between gastrointestinal abnormalities and ASD. Accordingly, we discuss gut microbiota dysbiosis regarding gut–brain axis dysfunction. On the other hand, this review suggests that probiotic administration to regulate the gut–brain axis might improve gastrointestinal symptoms, restore ASD-related behavioral symptoms, restore gut microbiota composition, reduce inflammation, and restore intestinal barrier function in human and animal models. This review suggests that targeting the microbiota through agents such as probiotics may represent an approach for treating subsets of individuals with ASD.